La tecnología se encuentra con la agricultura: Transición digital en América Latina - Bonilla, Melissa; Zapata, Emmanuel (2024)
A reflection on the multidisciplinary encounter held during the presentation of the book "Digital Transition in Agriculture and Public Policies in Latin America" within the framework of the international seminar of the same name that took place in Brasilia (Brazil) between December 4 and 6, 2024.